Pengendalian Sosial Penggunaan Smartphone Anak Bersekolah Di Madrasah Aliyah Babussalam Desa Peniraman - Sulaiman, Sulaiman (UNIVERSITAS TANJUNGPURA, 2019)
This thesis is entitled: social control by parents in the use of smartphones in children who are still in school at Madrasah Aliyah Babussalam Peniraman Pinyuh River District. The general problem of this research is social control by parents in the use of smartphones in children who are still in school at Madrasah Aliyah Babussalam Peniraman Pinyuh River sub-district. Sub problem in this research is 1: How persuasive social control by parents of children in the use of smartphones 2: How repressive social control by parents of children in the use of smartphones 3: How curative social control by parents of children in the use of smartphones. This study used a qualitative approach with descriptive methods. Observation data collection techniques, interviews and documentation study with data collection tool guide observation, interviews, books and archival records. Informal in this study are the parents and children. The positive impact for children to use the smartphone as to facilitate the child to seek material from school assignments, and berkomonikasi. But the negative impact of such children concentrate less on learning, lazy learning. The results of this research show that parents have been doing social control in children berifat persuasive, repressive and curative. But the negative impact of such children concentrate less on learning, lazy learning. The results of this research show that parents have been doing social control in children berifat persuasive, repressive and curative. But the negative impact of such children concentrate less on learning, lazy learning. The results of this research show that parents have been doing social control in children berifat persuasive, repressive and curative.